1988
DOI: 10.4278/0890-1171-2.4.23
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hazardous Lifestyles among Adolescents Based on Health-Risk Assessment Data

Abstract: The Rhode Island Department of Health has developed simple and convenient health risk appraisal (HRA) systems for adults, high-school students and college students. Using HRA data collected on 11,652 high-school students, this paper examines the discriminatory power of two mental health questions as predictors of high risk, unhealthy or dangerous behavior. Both questions, when examined separately, show that students who respond that "life is never worth living" and who report that "they never have emotional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The present study complements the work of Jessor and colleagues, who showed a clustering of problematic behaviors (e.g., Donovan & Jessor, 1985;Jessor & Jessor, 1977), as well as the work of Farberow and colleagues (e.g., Farberow, Stein, Darbonne, & Hirsch, 1970;Nelson & Farberow, in press;Farberow & Williams, 1980), who focused on the subtle self-destructive behaviors engaged in by some chronically ill adult and elderly patients. Also compatible with the broad conceptualization of suicidal behavior used in the present study, low social support and feelings of worthlessness have been found to be associated with both higher rates of health-compromising behaviors (e.g., driving while intoxicated, sunbathing) and lower rates of healthenhancing behaviors (e.g., toothbrushing, exercise) (Scott & Cabral, 1988). The broad focus taken in our definition of suicide proneness, specifically the inclusion of HR and IR domains, is also consistent with a move toward a more comprehensive view of health (e.g., Millstein, Petersen, & Nightingale, 1993).…”
Section: Suicide and Life-threatening Behaviorsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study complements the work of Jessor and colleagues, who showed a clustering of problematic behaviors (e.g., Donovan & Jessor, 1985;Jessor & Jessor, 1977), as well as the work of Farberow and colleagues (e.g., Farberow, Stein, Darbonne, & Hirsch, 1970;Nelson & Farberow, in press;Farberow & Williams, 1980), who focused on the subtle self-destructive behaviors engaged in by some chronically ill adult and elderly patients. Also compatible with the broad conceptualization of suicidal behavior used in the present study, low social support and feelings of worthlessness have been found to be associated with both higher rates of health-compromising behaviors (e.g., driving while intoxicated, sunbathing) and lower rates of healthenhancing behaviors (e.g., toothbrushing, exercise) (Scott & Cabral, 1988). The broad focus taken in our definition of suicide proneness, specifically the inclusion of HR and IR domains, is also consistent with a move toward a more comprehensive view of health (e.g., Millstein, Petersen, & Nightingale, 1993).…”
Section: Suicide and Life-threatening Behaviorsupporting
confidence: 86%
“…Adolescent engagement in suicidal and risk-taking behaviors has become a public health concern. Adolescent suicidal behavior in particular and risk-taking behaviors in general appear to be increasing in recent years (e.g., Scott & Cabral, 1988). Suicide is the second most frequent cause of death for adolescents 15-24 years of age (CDC, 1995), and accidents, which are frequently associated with risk-taking behaviors and substance use, are the leading cause of death in this age group (National Center for Health Statistics, 1991).…”
mentioning
confidence: 99%
“…Similarly, the link between personal and emotional factors and health risk behavior is well established. For example, depression has been linked with drug and alcohol use (Deykin, Levy, & Wells, 1987; Kandel & Davies, 1982; Scott & Cabral, 1988), poor impulse control with inability to assess riskiness accurately, and low self-esteem with infrequent use of contraceptives (Hayes, 1987). More specifically, Stiffman, Dore, Earls, and Cunningham (1992) showed that mental health symptoms were significantly correlated with risk behaviors among adolescents.…”
Section: Personal and Emotional Functioningmentioning
confidence: 99%